Walteri archidiaconi tervanensis Vita Karoli comitis Flandrie ; et Vita domni Ioannis Morinensis episcopi : quibus subiunguntur poemata aliqua de morte comitis Karoli conscripta et quaestio de eadem facta - Gautier, de Therouanne (Corpus Christianorum. Continuatio Mediaevalis, 2006)
"This volume revolves around three men who knew each other well, oversaw the political and spiritual life of much of northern France and Flanders during the first third of the twelfth century, and died within five years of one another: Charles the Good, count of Flanders from 1119 to 1127; John of Warneton, archdeacon of Arras from 1096 to 1099 and bishop of ThØrouanne from 1099 to 1130; and their common biographer, Walter, archdeacon of ThØrouanne from 1116 to 1132. The volume includes a detailed historical introduction and offers new editions of Walter's vit of Charles and John and of several other pieces - poems on Charles's death, his epitaphs, the record of the inquest into his murder - that, taken together with Walter's Vita Karoli and the edition of Galbert of Bruges' De multro, traditione, et occisione gloriosi Karoli comitis Flandriarum that has already appeared in this series (ed. J. RIDER, CC CM, 131, Turnhout, 1994), provide the most important elements of the dossier on Charles's assassination"